THE IMPORTANCE OF THE SCIENTIFIC HERITAGE OF ANCESTORS IN RAISING THE MORAL AND INTELLECTUAL POTENTIAL OF YOUNG PEOPLE - Valikhanova Gulnora Komiljonovna; Ahmedov Komiljon (Galaxy International Interdisciplinary Research Journal, 2023)
In the article, we talked about spiritual values, the importance of issues of scientific and spiritual heritage created by ancestors in today’s youth education, the sphere of influence. Scientific works created by Oriental allomas are analyzed from an educational point of view.